Radiation‐Induced Synthesis of Nanostructured Conjugated Polymers in Aqueous Solution: Fundamental Effect of Oxidizing Species. Issue 1 (18th December 2013) - Lattach, Youssef; Coletta, Cecilia; Ghosh, Srabanti; Remita, Samy
Abstract Synthesis of conjugated poly(3, 4‐ethylenedioxythiophene) (PEDOT) polymers is achieved through the radiolysis of N2O‐saturated aqueous solutions of 3, 4‐ethylenedioxythiophene by using two different oxidizing species: HO. (hydroxyl) and N3. (azide) radicals. Both oxidative species lead to self‐assembled polymers that are evidenced in solution by cryotransmission electron microscopy and UV/Vis absorption spectroscopy and, after centrifugation and deposition, by scanning electron microscopy and attenuated total reflectance FTIR techniques. Whereas HO. radicals lead to PEDOT‐OH globular nanostructures with hydrophilic properties, N3. radicals enable the formation of amphiphilic PEDOT‐N3 fibrillar nanostructures. These results, which highlight the differences in the intermolecular interaction behaviors of the two kinds of PEDOT polymers, are discussed in terms of polymerization mechanisms.